2014
DOI: 10.1371/journal.pone.0086742
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Marital Status in the Association between Benzodiazepines, Psychotropics and Injurious Road Traffic Crashes: A Register-Based Nationwide Study of Senior Drivers in Sweden

Abstract: BackgroundAmong senior drivers, benzodiazepines (BZDs) have a documented effect on the risk of road traffic crashes (RTCs). It remains unclear however if BZDs play the same role when considering marital status. Therefore, we aimed to investigate the role of marital status in the association between BZD use and injurious RTCs among senior drivers.MethodsMatched case-control study based on five national Swedish registers (n = 154 225). Cases comprised the first non-alcohol-related injurious RTC sustained by driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The association between the use of benzodiazepines and z‐hypnotics (zolpidem and zopiclone) and the risk of road traffic crashes has now been documented with consistent results in several epidemiological studies . In France, using a record‐linkage study of national databases, we showed that benzodiazepines and z‐hypnotics accounted for the largest share of the risk attributable to exposure to medicines .…”
Section: Introductionsupporting
confidence: 77%
“…The association between the use of benzodiazepines and z‐hypnotics (zolpidem and zopiclone) and the risk of road traffic crashes has now been documented with consistent results in several epidemiological studies . In France, using a record‐linkage study of national databases, we showed that benzodiazepines and z‐hypnotics accounted for the largest share of the risk attributable to exposure to medicines .…”
Section: Introductionsupporting
confidence: 77%
“…Prior studies in Brazil, the Netherlands, and Australia have linked benzodiazepine prescriptions-without a dose relationship-to patient selfreporting of poorer health status. [21][22][23] Benzodiazepine prescriptions were similarly linked to higher frequencies of medical diagnoses in two population-based Canadian studies, 40,41 and with a higher score on the Charlson comorbidity index in an Israeli study. 18 Studies linking benzodiazepines to a higher number of medical visits 21 and increased length of hospital stay 26 have been conducted in Israel and Japan, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…6,7,35 Senior patients are particularly vulnerable, because benzodiazepines are associated with falls, [36][37][38][39] hip fractures, 12 delirium, 10,11 disability, 13 dementia, 14,15 and motor vehicle accidents. 40 Osteoporosis has been linked to fractures alongside benzodiazepine prescriptions in The referent for odds ratios for diagnoses and other prescriptions is patients who did not have that diagnosis or prescription patients at risk of falls, although no direct relationship between osteoporosis and benzodiazepine prescriptions has been described. 41,42 Prescribing benzodiazepines disproportionately to patients with COPD, substance use disorders, and osteoporosis, and who are older may contribute to their mortality risk through these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of dosage during the day might also be of importance. Hypnotics and sedatives are taken before bedtime and may therefore exert influence only during sleep, whereas anxiolytics are used during day time and may therefore be more related to adverse outcomes such as day time excessive sedation, injuries, falls, and fractures (Johnell et al ., ).…”
Section: Discussionmentioning
confidence: 99%